COMPARISON OF ANTIOXIDATIVE POTENTIAL AND PUNICALAGIN CONTENT OF POMEGRANATE PEELS - A. A. Khalil1; M. R. Khan; M. A. Shabbir; K. U. Rahman (Journal of Animal and Plant Sciences, 2017)
Pomegranate peel has been traditionally used as folk medicine owing to rich source of polyphenolic compounds. Aim of present research was to assess total phenolics (TPC), total flavonoids (TFC) & punicalagin contents (PC) of pomegranate peels obtained from three different varieties for their application as nutraceutical ingredient in food preservation industry. Phytogenic rich fractions were extracted from Punica granatum L. (pomegranate) peel using solvent methanol. Moreover, methanolic extracts were characterized in vitro to evaluate their antioxidative potential using DPPH assay. Kandhari peel polyphenols inhibited 78.23% free radicals; though extracts of Badana peel displayed least antioxidant potential. Maximum phenolics and flavonoids were documented in Kandhari peel extracts as 289.40 mg/g GAE and 58.63 mg/g RE, correspondingly, however punicalagin (118.60 mg/g) was the most predominant ellagitannin quantified. Significant correlation (r = 0.999, 0.987; N = 3) was noticed amongst total phenolics, total flavonoids and antioxidative capacity of experimented varieties. Correlation analysis (r = 0.975; N = 3) proposed that punicalagin might be the bioactive compound responsible for antioxidant potential of extracts. Conclusively, the study illuminated the therapeutic and nutraceutical prospective & potential use of pomegranate peel as a cache of natural antioxidant.
Keywords: Phytogenic compounds; Antioxidants; Punicalagin; High performance liquid chromatography; Nutraceuticals